2020
DOI: 10.1038/s41598-020-70283-9
|View full text |Cite
|
Sign up to set email alerts
|

High efficiency electrocatalyst of LaCr0.5Fe0.5O3 nanoparticles on oxygen-evolution reaction

Abstract: Due to the multistep proton-coupled electron transfer, it remains a huge challenge to accelerate the kinetics of oxygen evolution reaction (OER). Here, we demonstrate that perovskite-type LaCr 0.5 Fe 0.5 O 3 nanoparticles can be used as highly active and stable OER electrocatalysts, where it shows a low overpotential of 390 mV at 10 mA/cm 2 , a small Tafel slope of 114.4 mV/dec and excellent stability with slight curren… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 34 publications
0
10
0
Order By: Relevance
“…72 This composition also displays excellent oxygen evaluation reaction (OER) performance. 73 The addition of manganese, La-Fe 1−x Mn x O 3 , drives a disorder induced localization of charge carriers. This in turn increases the overall electrical conductivity as a function of Mn content, up to x = 0.5.…”
Section: Structure Properties Of Lafeo 3 and Its Related Materialsmentioning
confidence: 99%
See 1 more Smart Citation
“…72 This composition also displays excellent oxygen evaluation reaction (OER) performance. 73 The addition of manganese, La-Fe 1−x Mn x O 3 , drives a disorder induced localization of charge carriers. This in turn increases the overall electrical conductivity as a function of Mn content, up to x = 0.5.…”
Section: Structure Properties Of Lafeo 3 and Its Related Materialsmentioning
confidence: 99%
“…The main composition of interest is LaFe 0.5 Cr 0.5 O 3 as the conductivity reaches a maximum . This composition also displays excellent oxygen evaluation reaction (OER) performance . The addition of manganese, LaFe 1– x Mn x O 3 , drives a disorder induced localization of charge carriers.…”
Section: Structure Properties Of Lafeo3 and Its Related Materialsmentioning
confidence: 99%
“…The conventional sol–gel used to develop the perovskite-type LaCr x Fe 1−x O 3 nanoparticle with a higher surface area for OER applications [ 94 ]. As shown in Figure 12 , the linear sweep voltammetry (LSV) of LaCr 0.5 Fe 0.5 O 3 reveals an OER overpotential of 390 mV at 10 mA/cm 2 , which is significantly lower than 510 mV of LaFeO 3 and 550 mV of LaCrO 3 .…”
Section: Perovskite Electrocatalysts With High Surface Areamentioning
confidence: 99%
“… ( a ) The polarization curves and ( b ) overpotential at 10 mA/cm 2 of LaFeO 3 , LaCrO 3 and LaCr 0.5 Fe 0.5 O 3 for OER. Copyright 2020 by the Springer Nature [ 94 ]. …”
Section: Figures and Schemementioning
confidence: 99%
“…Suntivich et al demonstrated that electrocatalytic activity for the ORR and OER is decided by some parameters, , like the number of 3d electrons and their spin state in transition metals, covalency of transition metal–oxygen bonds, positions of d-band centers of transition metals, and p-band centers of oxygen relative to the Fermi level, which can be changed by increasing the oxygen vacancy concentration and maintaining the redox couples. Some previous studies have proved that moderate oxygen vacancies in oxides can increase the electrocatalytic activity for the ORR and OER at room temperature. …”
Section: Introductionmentioning
confidence: 99%